2016
DOI: 10.3390/ijms17101633
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-375 Functions as a Tumor-Suppressor Gene in Gastric Cancer by Targeting Recepteur d’Origine Nantais

Abstract: Emerging evidence supports a fundamental role for microRNAs (miRNA) in regulating cancer metastasis. Recently, microRNA-375 (miR-375) was reported to be downregulated in many types of cancers, including gastric cancer. Increase in the expression of Recepteur d’Origine Nantais (RON), a receptor tyrosine kinase, has been reported in tumors. However, the function of miR-375 and RON expression in gastric cancer metastasis has not been sufficiently studied. In silico analysis identified miR-375 binding sites in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…miRNA-320b is down-regulated in various cancers, and it is associated with tumorigenesis and poor prognosis in glioma. 42 miRNA-375 was also shown to be often down-regulated in NSCLC, 43,44 breast cancer, 45 colorectal cancer, [46][47][48][49] oesophageal cancer, 50,51 gastric cancer, 52,53 and pancreatic cancer. 54,55 It is associated with tumour proliferation and metastases.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-320b is down-regulated in various cancers, and it is associated with tumorigenesis and poor prognosis in glioma. 42 miRNA-375 was also shown to be often down-regulated in NSCLC, 43,44 breast cancer, 45 colorectal cancer, [46][47][48][49] oesophageal cancer, 50,51 gastric cancer, 52,53 and pancreatic cancer. 54,55 It is associated with tumour proliferation and metastases.…”
Section: Discussionmentioning
confidence: 99%
“…GC is reported to be closely associated with the abnormal expression of miRNAs, including miR-375, miR-215 and miR-106a (2426). Various miRNAs have been identified as important regulators of tumorigenesis and cancer progression through diverse molecular pathways (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lian’ et al reported that miR-375 functions as a tumor-suppressor gene in gastric cancer by targeting recepteur d’Origine Nantais [20]. Xu and his colleagues showed that miR-375 suppresses human colorectal cancer metastasis by directly acting upon Frizzled 8, suggesting that this miRNA may serve as a new therapeutic target to inhibit colorectal cancer metastasis [21].…”
Section: Discussionmentioning
confidence: 99%